Combined immunodeficiency with marginal zone lymphoma due to a novel homozygous mutation in IL-21R gene and successful treatment with hematopoietic stem cell transplantation. (17th November 2021) - Edeer Karaca, Neslihan; Özek, Gülcihan; Ataseven, Eda; Tökmeci, Nazan; Şenol, Handan Duman; Kıran, Ezgi; Aykut, Ayça; Durmaz, Asude; Aksu, Güzide; Aksoylar, Serap; Aydoğdu, Sema; Çetingül, Nazan; et al.
Abstract: Mutations in the interleukin-21 receptor (IL-21R) gene are recently defined as primary immunodeficiency diseases. IL-21R defects result in combined immunodeficiency by affecting the functions of innate and adaptive immune system components. A six-year-old girl was admitted to our hospital with complaints of chronic diarrhea that started after the newborn period and generalized rash over the last three months. She had severe respiratory distress due to Cytomegalovirus (CMV) pneumonia requiring mechanical ventilation and was diagnosed as combined immunodeficiency at another hospital at the age of four. Her physical examination on admission revealed erythematous rash on cheeks, extremities, gluteal region, and lymph node enlargements in cervical, axillary, and inguinal regions. CMV DNA and stool Cryptosporidium parvum were positive. Marginal zone lymphoma –negative for Epstein-Bar virus– was reported in the lymph node biopsy. Targeted next-generation sequencing Ion AmpliSeq™ primary immunodeficiency panel revealed a novel homozygous IL21R c.132delC (p.Ser45fs) mutation. This case is presented to emphasize that IL21R defects should be considered in the differential diagnosis of the patients with recurrent respiratory infections, chronic diarrhea, C. parvum infection, chronic liver disease, sclerosing cholangitis, and malignancy where early hematopoietic stem cell transplantation (HSCT) is life-saving. A total of eight cases with IL21R gene defects have been reported so far. The significance of this case is that it is the first case of malignancy among the published IL-21R deficient patients successfully treated with HSCT.